A Study On Teaching-Learning Activities On Science At Smp Al-Islam Surakarta School Designed For International Standard In 2011/2012 Academic Year - Setianingsih, Sapta (2012)
The research aims at describing the teaching-learning activities at second grade of SMP Al-Islam Surakarta School Designed for International Standard in 2011/2012 Academic Year. It is conducted to describe the teaching-learning activities on Science at SMP Al-Islam Surakarta School Designed for International Standard in 2011/2012 Academic Year and the problems in teaching-learning activities at second grade of SMP Al-Islam Surakarta School Designed for International Standard in 2011/2012 Academic Year. The object of the study is the teaching-learning activities on Science at second grade of SMP Al-Islam Surakarta School Designed for International Standard in 2011/2012 Academic Year. The subject of the study is the Science teachers and students of second grade at RSBI class. The methods of collecting data are observation, interview, and documentation. In analysing data the writer applied descriptive qualitative research consisting of data reduction, data display, and drawing conclusion. The results of the study show the model of teaching-learning activities on Science of RSBI class belongs to immersion. Then, the syllabus and the lesson plan are designed in English. Furthermore, in teaching Science activities, the teachers deliver and explain the material to the students 50% in English and 50% in Indonesian. In addition, the teachers act as facilitator, material designer, and motivator. Then, the students roles are as an active learner and the listener. There problems faced by the teachers are the capability of the teachers, the capability of the students, and the complexity of the material.